Effects of Neurodevelopmental Therapy on Gross Motor Function in Children with Cerebral Palsy - LABAF, Sina (Iran J Child Neurol, 2015)
OBJECTIVE: Neurodevelopmental treatments are an advanced therapeutic approach practiced by experienced occupational therapists for the rehabilitation of children with cerebral palsy. The primary challenge in children with cerebral palsy is gross motor dysfunction. We studied the effects of neurodevelopmental therapy on gross motor function in children with cerebral palsy. MATERIALS & METHODS: In a quasi-experimental design, 28 children with cerebral palsy were randomly divided into two groups. Neurodevelopmental therapy was given to a first group (n=15) with a mean age of 4.9 years; and a second group with a mean age 4.4 years (n=13) who were the control group. All children were evaluated with the Gross Motor Function Measure. Treatments were scheduled for three - one-hour sessions per week for 3 months. RESULTS: We obtained statistically significant differences in the values between the baseline and post treatment in two groups. The groups were significantly different in laying and rolling (P=0.000), sitting (0.002), crawling and kneeling (0.004), and standing abilities (P=0.005). However, there were no significant differences in walking, running, and jumping abilities between the two groups (0.090). CONCLUSION: We concluded that the neurodevelopmental treatment improved gross motor function in children with cerebral palsy in four dimensions (laying and rolling, sitting, crawling and kneeling, and standing). However, walking, running, and jumping did not improve significantly.